Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - Chapter 1 Review Problem Set: 67

Answer

$9$

Work Step by Step

Substituting $a= -1 $ and $b= -3 ,$ the given expression, $ (a-b)-(a+b)-b ,$ evaluates to \begin{array}{l}\require{cancel} (-1-(-3))-(-1+(-3))-(-3) \\\\= (-1+3)-(-1-3)+3 \\\\= 2-(-4)+3 \\\\= 2+4+3 \\\\= 6+3 \\\\= 9 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.